Prodromal X‐Linked Dystonia‐Parkinsonism is Characterized by a Subclinical Motor Phenotype. Issue 7 (2nd May 2022) - Steinhardt, Julia; Hanssen, Henrike; Heldmann, Marcus; Sprenger, Andreas; Laabs, Björn‐Hergen; Domingo, Aloysius; Reyes, Charles Jourdan; Prasuhn, Jannik; Brand, Max; Rosales, Raymond; Münte, Thomas F.; Klein, Christine; et al.
Abstract: Background: Early diagnosis in patients with neurodegenerative disorders is crucial to initiate disease‐modifying therapies at a time point where progressive neurodegeneration can still be modified. Objectives: The objective of this study was to determine whether motor or non‐motor signs of the disease occur as indicators of a prodromal phase of X‐linked dystonia‐parkinsonism (XDP), a highly‐penetrant monogenic movement disorder with striking basal ganglia pathology. Methods: In addition to a comprehensive clinical assessment, sensor‐based balance and gait analyses were performed in non‐manifesting mutation carriers (NMCs), healthy controls (HCs), and patients with XDP. Gradient‐boosted trees (GBT) methodology was utilized to classify groups of interest. Results: There were no clinically overt disease manifestations in the NMCs. Balance analysis, however, revealed a classification accuracy of 90% for the comparison of NMC versus HC. For the gait analysis, the best‐performing GBT‐based model showed a balanced accuracy of 95% (NMC vs. HC; walking at maximum speed). Using a separate analysis of genetic modifiers, several gait parameters correlated strongly with the estimated age at disease onset in the NMC group. Conclusions: Our study unraveled balance and gait abnormalities in NMCs that preceded the onset of XDP. These findings demonstrate prodromal motor changes among NMCs who will develop XDP with a very high likelihood in the future. Gait abnormalities had a predictive value for the estimated age at onset highlighting the impact of genetic modifiers in personalized treatment in monogenic neurodegenerative disorders. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society